Biosecurity level and health management practices in 60 Swedish farrow-to-finish herds - Backhans, Annette (Acta Vet Scand, 2015)
BACKGROUND: Biosecurity measures are important tools to maintain animal health in pig herds. Within the MINAPIG project, whose overall aim is to evaluate strategies to raise pigs with less antimicrobial use, biosecurity was evaluated in medium to large farrow-to-finish pig herds in Sweden. In 60 farrow-to-finish herds with more than 100 sows, the biosecurity level was evaluated using a previously developed protocol (BioCheck). In a detailed questionnaire, internal and external biosecurity was scored in six subcategories each. An overall score for biosecurity was also provided. Information regarding production parameters as well as gender and educational level of personnel working with the pigs was also collected. Descriptive statistics were used to examine the recorded data. RESULTS: The median scores for external and internal biosecurity were 68 and 59, respectively, where 0 indicates total absence of biosecurity and 100 means maximal possible biosecurity. The subcategories for external and internal biosecurity that had the highest scores were “Purchase of animals” (external) and “Nursery unit”/“Fattening unit” (internal), while “Feed, water and equipment supplies” (external) and “Measures between compartments and equipment”/“Cleaning and disinfection” (internal) received the lowest scores. A female caretaker in the farrowing unit, a farmer with fewer years of experience and more educated personnel were positively associated with higher scores for some of the external and internal subcategories. In herds with <190 sows, fattening pigs were mixed between batches significantly more often than in larger herds. CONCLUSIONS: The herds in this study had a high level of external biosecurity, as well as good internal biosecurity. Strong biosecurity related to the purchase of animals, protocols for visitors, the use of all-in, all-out systems, and sanitary period between batches. Still, there is room for improvement in preventing both the introduction of disease to herds (external) and the spread of infections within herds (internal). Systems for animal transport can be improved and with respect to internal biosecurity, there is especially room for improvement regarding hygiene measures in and between compartments, as well as the staff’s working procedures between different groups of pigs. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s13028-015-0103-5) contains supplementary material, which is available to authorized users.